‘We have no services for you… so you have to make the best out of it’: A qualitative study of Myalgic Encephalomyelitis/Chronic Fatigue Syndrome patients’ dissatisfaction with healthcare services - Line Melby; Roshan das Nair (Health Expectations)
Abstract Introduction People should have access to healthcare services that are effective, safe and secure, patient‐centred, and coordinated and continuous. One group that has consistently reported negative experiences and feels dissatisfied with services are patients with Myalgic Encephalomyelitis (ME)/Chronic Fatigue Syndrome (CFS). The objective of this study was to develop a deeper understanding of the experiences of dissatisfaction among ME/CFS patients and explore the reasons for such dissatisfaction. Methods We conducted in‐depth interviews with 48 people from 24 households (comprising patients and family members), providing insight into the experiences of 37 ME/CFS sufferers in Norway. The participants were purposively sampled and included persons of different ages, genders, time since having the condition (3–30 years), and severity. Results Four main themes were developed: (1) ‘Nonexistent services’ cover patients’ experience that healthcare services had nothing to offer them after receiving their ME/CFS‐diagnosis. (2) ‘Nonpersonalised services’ documents experiences where patients did receive services, which in theory was appropriate for relieving a specific health problem, but in practice were experienced as inappropriate because they were not adapted to the patient's need. (3) ‘Slow services’ address patients’ experience of getting services too late (or too little) to be useful. (4) ‘Wrong services’ comprise patients’ experiences of being offered and/or ‘forced’ to accept services that they felt were inappropriate for their health problems. Conclusions Providers’ lacking knowledge of the condition and lack of precise recommendations for follow up may partly explain unsatisfactory experiences. Providers’ belief (or disbelief) in the condition could furthermore influence caregiving. Also, systemic issues in the healthcare sector, like high workloads and bureaucracy, can negatively affect care provision. Finally, users’ unsatisfactory experiences may also be due to a lack of patient involvement in the design of such services. Further research should investigate how patients can be involved in service design, and also providers’ perspectives on caregiving and the barriers they experience for providing high‐quality care. Patient or Public Contribution The ME‐patient organisation suggested research topics to the call from which this study got funding. Patients and caregivers provided feedback during analysis and interpretation of data.